Occurrences of gastrointestinal parasites in fecal samples from domestic dogs in São Paulo, SP, Brazil - Juliana Isabel Giuli da Silva Ferreira (Revista Brasileira de Parasitologia Veterinária, 2016)
Occurrences of gastrointestinal parasites were assessed in fecal samples from 3,099 dogs in the metropolitan region of São Paulo, SP, that were treated at the Veterinary Hospital of the University of São Paulo Veterinary School. The samples were analyzed using the flotation and centrifugal sedimentation methods. The results were compared with those from previous studies (at different times). The frequency of each parasite was correlated with the dogs’ ages, breeds and gender, as well as the occurrences of diarrhea and the use of anthelmintics, by means of the chi-square or Fisher exact test. Partitioned chi-square tests were used to compare occurrences of each parasite and the times analyzed. Out of the total number of samples, 20.5% were positive and 16.1% (102/635) of these presented more than one genus of parasites. Ancylostoma spp. (7.1%) and Giardia spp. (5.5%) were the most frequent helminths and protozoa, respectively. Ancylostoma spp. was associated (p<0.05) with age (over one year), mixed breeds, sex (male) and no use of anthelmintics. Dogs under one year and mixed breeds were associated with occurrences of Toxocara canis; and younger dogs with Giardia spp., Cryptosporidium spp. and Cystoisospora spp. Giardia spp. were also associated with dogs with a defined breed (p<0.05). All the parasites analyzed presented lower incidence in the last period analyzed than in the previous periods.